Working But Poor - A Cross-National Comparison of Earnings Adequacy - Inge O'Connor; Timothy Michael Smeeding (Luxembourg Income Study (LIS), 1993)
Compares the ability of prime-age, able-bodied workers in the U.S., Canada, Sweden, Netherlands, and the U.K. to keep themselves and their households out of poverty by working. The authors find that although the probability of being poor is smaller in households in which the head works full-year, full-time a substantial portion of poor households are working poor in all five countries.
Keywords: 330; Einkommen; Armut; Welt